Degradation of Chicken Feather a Poultry Waste Product by Keratinolytic Bacteria Isolated from Dumping Site at Ghazipur Poultry Processing Plant - Agrahari, Sarita; Wadhwa, Neeraj (International Journal of Poultry Science, 2010)
Feathers are byproduct waste of poultry processing plant and produced in large amount. A small percentage of feather waste is steamed, chemically treated, ground, to form feather meal a dietary protein supplement for animals. Alternatively, keratin can be biodegraded by some Keratinolytic bacteria and in this study Keratinase producing bacteria and their Keratinolytic enzyme production was investigated. Soil sample was collected from Ghazipur poultry waste site, Ghaziabad, India, a feather dumping site. Soil sample were inoculated in three enrichment media and colonies producing clear zone in feather meal agar were selected and identified as B. megaterium SN1, B. thuringenesis SN2, B. Pumilis SN3 were able to degrade chicken and pigeon feathers. They produced extracellularly Keratinolytic enzymes in enrichment media with 10% Feather meal powder. We report that Keratinase and Protease activity were detected in the culture supernatant and optimal medium for extracellular production of Keratinase and Protease is feather meal media 2 at pH (7.5) and temperature (30oC). There was complete degradation of feathers in 120 h of incubation and 0-80% Ammonium sulphate fraction showed 1.5 fold purification for Keratinase and 1.3 fold purification for Protease over the crude enzyme preparation. The keratinous waste can be biologically degraded by enzymes or the microbe itself to form useful products.